An efficient strategy of phosphorus recovery: Electrochemical pretreatment enhanced the anaerobic fermentation of waste activated sludge. (April 2021) - Xu, Yunfeng; Zhou, Qinghao; Wang, Xin; Yang, Min; Fang, Yangfan; Lu, Yongsheng
Abstract: The anaerobic fermentation (AF) of waste activated sludge (WAS) with an electrochemical pretreatment (EPT) was investigated to determine its correlation with the release of phosphorus and the disintegration of WAS. The sludge was pretreated by holding under 4.5 V for 60 min, followed by AF for 9 days. Untreated sludge was used as the control group (no-EPT). Results showed that, with pretreatment, the total dissolved P (TDP), orthophosphate (PO4 3- -P) and organic P (OP) reached the maximum values of 7.30 mg/L, 4.77 mg/L and 2.35 mg/L on day 8, respectively, which were approximately 5.3, 9.2 and 2.7 times greater than that in the control group. The analysis of soluble chemical oxygen demand (SCOD), protein and polysaccharides showed that the EPT promoted the disintegration of sludge, thereby enhancing the P release. The SCOD reached 1625 mg/L on day 6 in pretreatment experiment, which was about 9.8 times greater than that in control group. Additionally, the EPT contributed to fewer metal ions in sludge supernatant. This mechanism might have been due to the anions accumulating in the supernatant from the greater degree of sludge collapse after EPT, which caused the released metal ions to combine with anions to form insoluble compounds. In conclusion, EPT could be a promising method for the dissolution of sludge and the recovery of phosphorus from WAS under AF. Besides, the economic benefit evaluation showed the potential value of EPT for P recovery. Graphical abstract: Image 1 Highlights: Higher content of phosphorus could be achieved by electrochemical pretreatment (EPT) from WAS during AF. Soluble chemical oxygen demand (SCOD) was 9.8 times than raw sludge. EPT could lead to lower metal ions in liquid phase. There will be a considerable economic value to recover phosphorus according to the EPT enhanced anaerobic digestion method.